Development of 68Ga-Labeled Hepatitis E Virus Nanoparticles for Targeted Drug Delivery and Diagnostics with PET - Lambidis, Elisavet; Chen, Chun-Chieh; Baikoghli, Mo; Imlimthan, Surachet; Khng, You Cheng; Sarparanta, Mirkka; Cheng, R. Holland; Airaksinen, Anu J. (Molecular pharmaceutics, 2022)
Targeted delivery of diagnostics and therapeutics offers essential advantages over nontargeted systemic delivery. These include the reduction of toxicity, the ability to reach sites beyond biological barriers, and the delivery of higher cargo concentrations to diseased sites. Virus-like particles (VLPs) can efficiently be used for targeted delivery purposes. VLPs are derived from the coat proteins of viral capsids. They are self-assembled, biodegradable, and homogeneously distributed. In this study, hepatitis E virus (HEV) VLP derivatives, hepatitis E virus nanoparticles (HEVNPs), were radiolabeled with gallium-68, and consequently, the biodistribution of the labeled [68Ga]Ga-DOTA-HEVNPs was studied in mice. The results indicated that [68Ga]Ga-DOTA-HEVNPs can be considered as promising theranostic nanocarriers, especially for hepatocyte-targeting therapies.